2014
DOI: 10.1007/s00590-014-1502-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing complications of vertebroplasty and kyphoplasty for treating osteoporotic vertebral compression fractures: a meta-analysis of the randomized and non-randomized controlled studies

Abstract: The two procedures suffer from equal risk of subsequent spinal fractures; PVP has a significant higher cement leakage rate compared to BKP, mainly caused by a higher paravertebral leakage, patients with extremely poor pulmonary function or unstable haemodynamic are better candidates for BKP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 29 publications
1
19
0
3
Order By: Relevance
“…Complications associated with treatment of OVCFs in previous reports 35,36 were left outside the scope of this meta-analysis. Although not considered in this review, there are rare but potentially devastating complications associated with PVP, such as cement leakage leading to pulmonary embolism, or recurrent fractures [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with treatment of OVCFs in previous reports 35,36 were left outside the scope of this meta-analysis. Although not considered in this review, there are rare but potentially devastating complications associated with PVP, such as cement leakage leading to pulmonary embolism, or recurrent fractures [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…30 Yet cement leakage in the ‘at-risk’ disc space was no different between the two methods of augmentation while the ‘safe’ paravertebral space showed reduction of leakage in the kyphoplasty. 31 …”
Section: The Best Methods Of Cement Augmentation For Ovfsmentioning
confidence: 99%
“…Another factor related by some authors to an increase in new fractures is the recovery of vertebral height achieved with KP. However, a recent meta-analysis published by Xiao et al 16 has concluded that there are no differences between both the surgical techniques in for risk of subsequent fracture.…”
Section: Adjacent Vfs and Repeat Fracturesmentioning
confidence: 97%